Data Analytics based Gender stereotypes represented in the audiovisual narrative of the series "You" - Jeri Condori, Nataly Silvana (2022)
This research analyzes gender stereotypes in the audiovisual narrative of the first season of the series You. The objective is to describe the components of the masculine and feminine archetypes represented in the main characters. For this purpose, the qualitative methodology, the case study method, as well as observation and focus group techniques were used. Likewise, observation sheets were applied to detect psychosocial characteristics such as traits, roles, motivations, and behaviors in the archetypes. In the focus groups, through an interview guide, the impressions of students between 19 and 25 years old in Lima, Peru, were collected. The results were analyzed through data reduction. The research showed that gender stereotypes were represented through male and female archetypes in the main characters. Likewise, their psychosocial characteristics such as traits, roles, motivations, and behaviors were identified and classified as negative and positive.